Multi-Branched Thoracoabdominal Endovascular Aortic Repair With Branch Access Through a Left Thoracotomy and Descending Thoracic Aortic Conduit: A Novel and Effective Alternative Access. (December 2022) - Ferreira, Marcelo; Mannarino, Matheus; Cunha, Rodrigo; Ferreira, Diego; Capotorto, Luis Fernando
Purpose: To demonstrate an alternative access to perform directional branch catheterization during complex endovascular aortic repair. Technique: Urgent endovascular aortic repair was indicated to treat a symptomatic post dissection thoracoabdominal aneurysm with large infrarenal dilatation with an off-the-shelf t-Branch endograft (Cook Medical, Bloomington, IN, USA). Traditional proximal arterial accesses were not suitable due to a previous aortic arch endograft. A novel approach was performed through a left postero-lateral thoracotomy, isolation of the descending thoracic aorta and anastomosed a polyester graft conduit to allow sheaths passage to the thoracoabdominal aorta with subsequently directional branch catheterization. Conclusion: The descending thoracic aortic conduit technique is an effective alternative for directional branch catheterization and should be considered whenever traditional proximal arterial accesses are not suitable and other endografts configurations not considered due to anatomic limitations.